The Effects Of Mudharabah And Musyarakah Financing On The Profitability Of Sharia Commercial Banks In Indonesia - Arsyadona Arsyadona; Saparuddin Siregar; Isnaini Harahap; M Ridwan (Proceeding International Seminar of Islamic Studies, 2019)
: This research was conducted to determine the effect of mudharabah and musharakah profit sharing financing on the profitability of Islamic commercial banks in Indonesia. This study uses the annual Islamic Commercial Bank financial reports obtained from the Financial Services Authority (Otoritas Jasa Keuangan) for the period 2015-2019. The test results using SPSS 25 show that both mudharabah and musyarakah financing have a significant effect on the profitability of Islamic banks. But unlike musyarakah financing, mudharabah financing actually has a negative effect on profitability, meaning that the higher an Islamic bank distributes mudharabah financing, the rate of profit will decrease.